2017
DOI: 10.1128/mbio.00470-17
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiota Mediates the Protective Effects of Dietary Capsaicin against Chronic Low-Grade Inflammation and Associated Obesity Induced by High-Fat Diet

Abstract: Metabolic endotoxemia originating from dysbiotic gut microbiota has been identified as a primary mediator for triggering the chronic low-grade inflammation (CLGI) responsible for the development of obesity. Capsaicin (CAP) is the major pungent bioactivator in chili peppers and has potent anti-obesity functions, yet the mechanisms linking this effect to gut microbiota remain obscure. Here we show that mice fed a high-fat diet (HFD) supplemented with CAP exhibit lower levels of metabolic endotoxemia and CLGI ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
200
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 41 publications
(68 reference statements)
6
200
1
1
Order By: Relevance
“…The blood samples were collected after 4 h and then centrifuged at 6,000 × rpm for 10 min at 4 °C. The serum was diluted with the same volume of PBS and analyzed for FITC‐dextran with a SpectraMax M2 microplate reader (Molecular Devices, USA) which with an excitation wavelength at 485 nm and an emission wavelength at 535 nm as previously described . Standard curves were used for calculating the samples FITC‐dextran concentration through a serial dilution of FITC‐dextran in PBS (0 ≈ 12.5 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The blood samples were collected after 4 h and then centrifuged at 6,000 × rpm for 10 min at 4 °C. The serum was diluted with the same volume of PBS and analyzed for FITC‐dextran with a SpectraMax M2 microplate reader (Molecular Devices, USA) which with an excitation wavelength at 485 nm and an emission wavelength at 535 nm as previously described . Standard curves were used for calculating the samples FITC‐dextran concentration through a serial dilution of FITC‐dextran in PBS (0 ≈ 12.5 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Liver homogenates were obtained by a tissue homogenizer (IKA, Germany). According to the manufacturer's protocol, Limulus amebocyte lysate reagents were added to plasma and liver homogenates . All of the samples were tested in duplicate, and optical density values were measured using a SpectraMax M2 microplate reader (Molecular Devices, USA) at a wavelength of 545 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HFD‐induced obesity in mice is accompanied by an increase in bacteria of the family Lachnospiraceae . In contrast, Kang and colleagues showed that the anti‐obesity effects of capsaicin could be partially mediated through an increased abundance of Lachnospiraceae in HFD‐fed mice. Moreover, Menni and colleagues found a lower long‐term weight gain associated with this family in humans.…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%